Phenotypic heterogeneity and diagnostic features of transthyretin amyloidosis with polyneuropathy - S. S. Nikitin; S. N. Bardakov; N. A. Suponeva; I. V. Zhirov; T. A. Adyan; D. A. Grishina; R. V. Deev (Нервно-мышечные болезни, 2021)
Transthyretin amyloidosis (ATTR-amyloidosis) is a systemic progressive fatal disease, for which a modifying therapy has recently been proposed that delays the progression of the disease and improves the patient’s quality of life. The delay in the diagnosis of ATTR-amyloidosis is associated with the heterogeneity of the manifestations of the disease, as well as insufficient awareness of doctors of different specialties about the disease. A review of recent studies on the symptomatology, diagnosis, molecular genetic characteristics of ATTR-amyloidosis and the most common forms of the disease with the predominant involvement of peripheral nerves and the heart, as well as the kidneys, gastrointestinal tract, and eyes is presented. The international consensus recommendations for the diagnosis of suspected ATTR-amyloidosis using modern methods that facilitate early and accurate diagnosis are discussed. The reasons and the most frequent misdiagnoses of ATTR-amyloidosis, which also lead to a delay in the timely appointment of therapy, are considered. Molecular genetic testing should be considered early in the evaluation of a patient with unexplained peripheral neuropathy and cardiomyopathy. A diagnostic algorithm based on the initial symptoms and manifestations of the cardiovascular and nervous systems facilitates the identification of a patient with clinical suspicion of ATTR-amyloidosis by the general practitioner. Early diagnosis is critically important for patients with ATTR polyneuropathy, since the early prescription of Vyndaqel (tafamidis), registered in the Russian Federation in 2017, allows a significant clinical effect to be obtained. Timely administration of Vyndaqel significantly slows down the progression of the disease, improves the prognosis and quality of life in patients with ATTR polyneuropathy.